2017
DOI: 10.1016/j.ccell.2017.01.014
|View full text |Cite
|
Sign up to set email alerts
|

A Kinase Inhibitor Targeted to mTORC1 Drives Regression in Glioblastoma

Abstract: SUMMARY Although signaling from PI3K and AKT to mTOR is prominently dysregulated in high-grade glial brain tumors, blockade of PI3K or AKT minimally affects downstream mTOR activity in glioma. Allosteric mTOR inhibitors, such as rapamycin, incompletely block mTORC1 compared to mTOR kinase inhibitors (TORKi). Here, we compared RapaLink-1, a TORKi linked to rapamycin, with earlier generation mTOR inhibitors. Compared to rapamycin and Rapalink-1, TORKi showed poor durability. RapaLink-1 associated with FKBP12, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
140
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(149 citation statements)
references
References 28 publications
8
140
1
Order By: Relevance
“…Thus, the RapaLink design may more effectively delay the acquisition of mTOR resistance mechanisms. A follow up study highlighted two additional advantages of RapaLinks compared to TORKi (Fan et al, 2017). First, RapaLinks are somewhat selective for mTORC1 versus mTORC2 (Figure 2), possibly reducing toxicities associated with mTORC2 inhibition.…”
Section: Therapeutic Targeting Of the Pi3k Pathway In Cancermentioning
confidence: 99%
“…Thus, the RapaLink design may more effectively delay the acquisition of mTOR resistance mechanisms. A follow up study highlighted two additional advantages of RapaLinks compared to TORKi (Fan et al, 2017). First, RapaLinks are somewhat selective for mTORC1 versus mTORC2 (Figure 2), possibly reducing toxicities associated with mTORC2 inhibition.…”
Section: Therapeutic Targeting Of the Pi3k Pathway In Cancermentioning
confidence: 99%
“…As expected, following mTOR deletion, PreT-OPC reactivation is unaffected but malignant transformation is completely blocked. Encouragingly, very recently a new class of mTOR inhibitor that can effectively penetrate BBB and inhibit mTOR kinase activity was found to have significant anti-tumor effects on glioma cells (Fan et al, 2017). One conceivable explanation is that, since mTOR KO is restricted to OPCs while the drug works on all cell types, the inhibition of OPC reactivation by the drug could go through non-cell autonomous mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, while past trials with mTOR inhibitors for glioma patients showed limited efficacy, further studies demonstrated that most of these failures were caused by the inability of the drugs to effectively penetrate the blood-brain barrier (BBB) or to adequately inhibit their targets (Cloughesy et al, 2008;Rodrik-Outmezguine et al, 2016). Encouragingly, very recently a new class of mTOR inhibitor that can effectively penetrate BBB and inhibit mTOR kinase activity was found to have significant anti-tumor effects on glioma cells (Fan et al, 2017). Our data echo well with these findings and the existing knowledge of mTOR's critical role in OPC development (Guardiola-Diaz, Ishii, & Bansal, 2012), thus provide strong rationales for further testing of mTOR inhibitors in glioma patients.…”
Section: Discussionmentioning
confidence: 99%
“…B, Schematic diagrams illustrating how allosteric driver mutations release autoinhibition. For this reason, reversing it by allosteric noncovalent [147][148][149] and covalent 150,151 drugs is also a formidable pharmacological task. Allosteric inhibitors require the autoinhibited conformation.…”
Section: Conclusion: Are Autoinhibited States Good Targets For Drumentioning
confidence: 99%